2020
DOI: 10.3389/fneur.2020.00709
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia Gravis Masquerading as an Idiopathic Unilateral Facial Paralysis (Bell's Palsy)—A Very Rare and Unique Clinical Find

Abstract: Myasthenia gravis (MG) is an uncommon autoimmune neuromuscular junction disorder manifesting as fluctuating weakness of skeletal muscles. To add to its repertoire of mimicking a wide range of neurological disorders, the present case report is, to the best of our knowledge, the very first to describe MG masquerading as an idiopathic unilateral facial paralysis (Bell's palsy, BP). Our case report is distinct, highlights a novel clinical occurrence, offers new insights of how different neurological disorders may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Th2 cells mediate humoral immunity by secreting cytokines such as IL-4, IL-6, and IL-10. IL-4 is a multifunctional and multieffect cytokine, which may not cause disease or even have protective effect in the pathogenesis of MG. Elnazeir et al found that the downregulation of IL-4 level may be related to the development of MG symptoms by detecting the concentration of IL-4 in peripheral blood of 47 patients with MG [ 5 ]. IL-6 can induce the transformation of Treg cells to pathogenic Th17 cells and promote the production of antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Th2 cells mediate humoral immunity by secreting cytokines such as IL-4, IL-6, and IL-10. IL-4 is a multifunctional and multieffect cytokine, which may not cause disease or even have protective effect in the pathogenesis of MG. Elnazeir et al found that the downregulation of IL-4 level may be related to the development of MG symptoms by detecting the concentration of IL-4 in peripheral blood of 47 patients with MG [ 5 ]. IL-6 can induce the transformation of Treg cells to pathogenic Th17 cells and promote the production of antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant MG manifestation is caused by autoantibodies that bind to the acetylcholine receptors (AChR) or to functionally related postsynaptic membrane molecules of the NMJ resulting in cholinergic transmission impairment. It has been suggested that the cholinergic deficit in MG may affect other regions as well, making the disease a “neurologic chameleon” able to mimic RRMS symptoms [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unilateral presentation of MG is rare but has been documented on a few occasions [ 15 , 16 ]. When our patient initially presented to the emergency department, he was treated for Bell’s palsy.…”
Section: Discussionmentioning
confidence: 99%